Keratoconus and Ectatic Disease: Evolving Criteria for Diagnosis - Belin, Michael Wellington (Klinische Monatsblätter für Augenheilkunde, 2020)
The approach to corneal ectatic disease has changed dramatically over the last decade with advances in both diagnosis and treatment. Newer treatments, such as corneal cross-linking, have the potential to slow or stop the progression of the disease, but benefit from earlier identification of the disease than had previously been possible or required. The continued use of older diagnostic criteria and ambiguous terminology can lead to erroneous study conclusions that may not be applicable to patients with true pathology.
Keywords: keratoconus; pellucid marginal degeneration; ectatic disease; topography; tomography